472 days captive of the Abu Sayyaf the survival of Australian Warren Rodwell - East, Bob (Conflict researcher) (Cambridge Scholars Publishing, 2015)
In December 2011, the Australian world traveller, ex-member of the Australian Regular Army and university teacher Warren Richard Rodwell was kidnapped for ransom in the Mindanao region of the southern Philippines by a group of criminals claiming to be members of the notorious terrorist/insurgent organisation the Abu Sayyaf Group. This particular group had loose ties with other insurgent groups that were indulging in similar criminal activity in the greater Sulu Archipelago area including the Zamboanga peninsular -- where Rodwell was abducted. Rodwell was kept prisoner for a total of 472 days making him the longest held Australian captive outside of official Prisoners-of-War (POWs).